2017
DOI: 10.1021/acs.jpcc.7b10280
|View full text |Cite
|
Sign up to set email alerts
|

Linear Tunability of the Band Gap and Two-Dimensional (2D) to Three-Dimensional (3D) Isostructural Transition in WSe2 under High Pressure

Abstract: Transition metal dichalcogenides (TMDs) have recently gained tremendous interest for use in electronic and optoelectronic applications. Unfortunately, the electronic structure or band gap of most TMDs shows noncontinuously tunable characteristics, which limits their application to energy-variable optoelectronics. Thus, layered materials with better tunability in their electronic structures and band gaps are desired. Herein, we experimentally demonstrated that layered WSe2 possessed highly tunable transport pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 53 publications
0
26
0
Order By: Relevance
“…6,19,20,29,51,52 Previous investigations on 2D transition-metal dichalcogenides, such as TX 2 (T = Mo and W and X = S, Se, and Te) having fundamental band gap values of about 1.1−1.4 eV, showed that they turn to metals when subjected to high-pressure application above 40−60 GPa in WSe 2 , 53−55 36−37 GPa in WS 2 , 56,57 30−40 GPa in MoSe 2 , 58,59 19 GPa in MoTe 2 , 58 and above 20−40 GPa in MoS 2 . 60−65 These semiconductor−metal transitions either were accompanied by isostructural transformations [54][55][56]60,63,64 or happened without structural changes. 58,59 High-pressure structural investigations on TiS 3 demonstrated that its original ZrSe 3 -type lattice persists under compression up to 22 GPa, and beyond this point, it suffers to an isosymmetric transition.…”
Section: Introductionmentioning
confidence: 99%
“…6,19,20,29,51,52 Previous investigations on 2D transition-metal dichalcogenides, such as TX 2 (T = Mo and W and X = S, Se, and Te) having fundamental band gap values of about 1.1−1.4 eV, showed that they turn to metals when subjected to high-pressure application above 40−60 GPa in WSe 2 , 53−55 36−37 GPa in WS 2 , 56,57 30−40 GPa in MoSe 2 , 58,59 19 GPa in MoTe 2 , 58 and above 20−40 GPa in MoS 2 . 60−65 These semiconductor−metal transitions either were accompanied by isostructural transformations [54][55][56]60,63,64 or happened without structural changes. 58,59 High-pressure structural investigations on TiS 3 demonstrated that its original ZrSe 3 -type lattice persists under compression up to 22 GPa, and beyond this point, it suffers to an isosymmetric transition.…”
Section: Introductionmentioning
confidence: 99%
“…High-pressure not only enables an in-depth understanding of the structure-property relations for 2D materials and corresponding heterostructures but also modifies their optoelectronic properties. [14,17,20,48,167,[201][202][203] These high-pressure phased properties through vdW interaction engineering extend the potential applications of 2D materials in optical, electronic, and optoelectronic fields. [16] Although some optimized properties might not be retained after releasing the pressure, they are instructive for the synthesis of new 2D materials as well as designs of novel functional devices under high pressure.…”
Section: Optimized Optoelectronic Properties and Potential Applicationsmentioning
confidence: 89%
“…It shows a slow-down drop of resistance and a tendency toward a low-temperature curve with the increase of magnetic fields, proving the emergence of the superconducting phase. [180] Chi et al also investigated the www.advancedsciencenews.com www.advancedscience.com [39] (CH 3 NH 3 )PbI 3 Above 60 (RT) [42] Cs 3 Bi 2 I 9 28 (338 K) [ 200] 2D TMDs ZrTe 2 T-ZrTe 2 ≈ 2 (H-Zr-Te 2 ≈ 6) [ 201] 1T-TiSe 2 2-4 (1.8 K) [ 191] WTe 2 10.5 (2.8 K); [ 183] 4-5 (300 K) [ 184] WS 2 22 (280 K) [17] WSe 2 51.7 (RT) [ 202] ZrS 2 5.6-25 [ 186] 5.6-25 (1.1-1.9 K) or 25-100 (0.3-0.1 K) [ 186] MoTe 2 14.9 [ 203] MoS 2 30 (270 K); [ 167] 9 (RT) [19] 90 (3 K) [ 167] Intermediate state: 10-19; semiconducting state: 0-10 [19] CdI 2 62 (240 K) [ 174] 35 (270 K) [ 174] semiconducting phase FeCL 2 47 (300 K) [ 204] NI 2 19 (310 K) [ 205] MgC 2 Ambient pressure (15 K) [ 206] BP 1.7, 10 [ 207] Above 5 (6-13 K); [ 181] above 10 (5-10 K); [ 182] 11-30 (4-10.7 K), 15 (6 K) [ 207] MoSe 2 40.7-60 [20] 0-40.7 semiconducting phase CaC 2 43 (7.9 K) and 95 (9.8 K) [ 185] CaC 6 7.5 (15.1 K) [ 208] superconductivity in pristine 2H a -MoS 2 and this is explained by the occurrence of a new flat Fermi pocket at ultrahigh pressure. [167] Using the external magnetic field, superconductivity was again verified.…”
Section: Superconductingmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the Raman frequencies are very sensitive to strain, in situ Raman spectra were measured upon compression to probe subtle local changes of lattice vibrations. 39 The lowfrequency and high-frequency modes are associated with the inorganic PbBr 6 octahedral network and organic CH 3 (CH 2 ) 3 NH 3 cations, respectively. 40 Previous work suggests that the modes of PbBr 6 rotations and distortions dominate the low-frequency Raman spectra.…”
mentioning
confidence: 99%